From Bias To Justice: “Reconstructing The Interpretation Of Qawwam (Leadership) In The Al-Qur'an From Amina Wadud's Perspective - Ahmad Zabidi; Sri Sunantri; Maulana (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This article attempts to discuss the differences in understanding the meaning of qawwam. Due to seeing various phenomena that occur in society in everyday life, there are always different points of view in understanding the verses of the Qur’an, including the issue of understanding leaders in the Qur’an by Amina Wadud. Amina Wadud is one of the current contemporary figures who supports gender. Amina Wadud is a feminist activist, her monumental book is entitled Qur'an and Women: Rerading the Sacred Text from a Women's Perspective. Amina Wadud directs a deconstructive style of interpretation towards laws that are widely known by Muslims such as inheritance, the role of women, nusyuz, including the issue of imams (leaders) regardless of the pros and cons among the ulama. This issue is very interesting to research regarding the reconstruction of the understanding of the verse about the meaning of qawwam in the Qur’an by looking at the figure of a woman named Amina Wadud. With gender understanding which assumes that men and women are equal before Allah SWT. Amina Wadud wants to revive the role of women in equality in gender relations, based on the principles of social justice and gender equality. Reality in Islam shows the reason why women are more backward than men (patriarchy). Amina Wadud saves women from Islamic conservatism. According to him, there are many things that cause skewed interpretations about women, societal culture, paradigm errors, and the background of the interpreters, most of whom are men. Therefore, the verses about leaders should be interpreted by women themselves based on their perceptions, experiences and thoughts